Players over the Surface: Unraveling the Role of Exopolysaccharides in Zinc Biosorption by Fluorescent Pseudomonas Strain Psd - Upadhyay, Anamika; Kochar, Mandira; Rajam, Manchikatla V.; Srivastava, Sheela (Frontiers in Microbiology, 2017)
Fluorescent Pseudomonas strain Psd is a soil isolate, possessing multiple plant growth promoting (PGP) properties and biocontrol potential. In addition, the strain also possesses high Zn2+ biosorption capability. In this study, we have investigated the role exopolysaccharides (EPS) play in Zn2+ biosorption. We have identified that alginates are the prime components contributing to Zn2+ biosorption. Deletion of the alg8 gene, which codes for a sub-unit of alginate polymerase, led to a significant reduction in EPS production by the organism. We have also demonstrated that the increased alginate production in response to Zn2+ exposure leads to improved biofilm formation by the strain. In the alg8 deletion mutant, however, biofilm formation was severely compromised. Further, we have studied the functional implications of Zn2+ biosorption by Pseudomonas strain Psd by demonstrating the effect on the PGP and biocontrol potential of the strain.